Safety and Efficacy of Adding Fixed-Combination Brinzolamide/Timolol Maleate to Prostaglandin Therapy for Treatment of Ocular Hypertension or Glaucoma - Hommer, Anton (J Ophthalmol, 2015)
Purpose. To evaluate the safety and efficacy of adding brinzolamide 1%/timolol maleate 0.5% fixed combination (BTFC) to a prostaglandin analog (PGA). Methods. This was a 12-week, open-label, single-arm study of patients with open-angle glaucoma or ocular hypertension with intraocular pressure (IOP) not sufficiently controlled after ≥4 weeks of PGA monotherapy. The primary outcome was mean IOP change from baseline at week 12. Other outcomes included IOP change from baseline at week 4, percentage of patients achieving IOP ≤18 mmHg at week 12, and patient experience survey responses at week 12. Results. Forty-seven patients were enrolled and received treatment. The most commonly used PGAs were latanoprost (47%) and travoprost (32%). Mean ± SD IOP was decreased at week 12 (17.2 ± 4.1 mmHg) compared with baseline (23.1 ± 3.0 mmHg; P < 0.001, paired t-test); IOP at week 4 was 17.2 ± 3.3 mmHg. At week 12, 70% of patients achieved IOP ≤18 mmHg. Patient-reported symptoms (e.g., pain and redness) were mostly unchanged from baseline. Twenty-eight adverse events (AEs) were reported; the most frequently reported AE was headache (3 events in 2 patients). Conclusion. Adjunctive BTFC + PGA therapy was effective and well tolerated. IOP decreased by 6 mmHg at weeks 4 and 12.